2023
DOI: 10.3390/ijms24054770
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Synthesis of Magnetic Nanoparticles Based on Iron Oxides Using Orange Waste and Their Application as Photo-Activated Antibacterial Agents

Abstract: Magnetic nanoparticles based on iron oxides (MNPs-Fe) have been proposed as photothermal agents (PTAs) within antibacterial photothermal therapy (PTT), aiming to counteract the vast health problem of multidrug-resistant bacterial infections. We present a quick and easy green synthesis (GS) to prepare MNPs-Fe harnessing waste. Orange peel extract (organic compounds) was used as a reducing, capping, and stabilizing agent in the GS, which employed microwave (MW) irradiation to reduce the synthesis time. The produ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 107 publications
0
1
0
Order By: Relevance
“…A new effort to expand the use of agro-wastes as sources of biomolecules in green nanotechnology has received considerable attention, and various agro-wastes have been documented for their relevance in nanobiotechnology [145]. As a result, a range of metallic nanoparticles have been successfully synthesized from agro-industrial wastes, and extracts from these residues have been employed as reducing and stabilizing agents in the majority of cases [146]. The nanoparticles produced in this way have a wide range of activities, including antimicrobial, antioxidant, anticorrosive, and cytotoxic against cancer cells, among others [146][147][148][149].…”
Section: Green Synthesis Of Iron Oxide Nanoparticles Using From Biolo...mentioning
confidence: 99%
See 1 more Smart Citation
“…A new effort to expand the use of agro-wastes as sources of biomolecules in green nanotechnology has received considerable attention, and various agro-wastes have been documented for their relevance in nanobiotechnology [145]. As a result, a range of metallic nanoparticles have been successfully synthesized from agro-industrial wastes, and extracts from these residues have been employed as reducing and stabilizing agents in the majority of cases [146]. The nanoparticles produced in this way have a wide range of activities, including antimicrobial, antioxidant, anticorrosive, and cytotoxic against cancer cells, among others [146][147][148][149].…”
Section: Green Synthesis Of Iron Oxide Nanoparticles Using From Biolo...mentioning
confidence: 99%
“…As a result, a range of metallic nanoparticles have been successfully synthesized from agro-industrial wastes, and extracts from these residues have been employed as reducing and stabilizing agents in the majority of cases [146]. The nanoparticles produced in this way have a wide range of activities, including antimicrobial, antioxidant, anticorrosive, and cytotoxic against cancer cells, among others [146][147][148][149]. In general, extracts containing active biomolecules that promote the formation of nanoparticles can be prepared using a simple hot water extraction process of dried and ground agrowaste materials [145].…”
Section: Green Synthesis Of Iron Oxide Nanoparticles Using From Biolo...mentioning
confidence: 99%
“…Das et al synthesized carbon dots from Apium graveolens , which were demonstrated as effective hydrogels against bactericidal activities, and controlled release of phytomedicines [ 24 ]. García et al synthesized magnetic NPs based on iron oxide from wastes of oranges, which had shown antibacterial activities [ 25 ]. Lyu et al prepared mannose-coated serum albumin NPs which targeted neutrophils for the therapy of arthritis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%